Where have all the GPs gone – where will they go? Study of Finnish GPs - Sumanen Markku; Aine Tiina; Halila Hannu; Heikkilä Teppo; Hyppölä Harri; Kujala Santero; Vänskä Jukka; Virjo Irma; Mattila Kari (BMC Family Practice, 2012)
Abstract Background In this paper a specialist in general practice is referred to as a general practitioner (GP). In Finland only half of all GPs work as a health centre physician. The present aim was to establish what the working places of specializing and specialized physicians in general practice are, and where they assume they will work in the future. Methods The study population comprised 5,357 physicians licensed in Finland during the years 1977–1996. Altogether 2,956 questionnaires were returned, a response rate of 55.2%. Those either specializing (GP trainees, n=133) or already having specialized (GPs, n=426) in general practice were included in the study. Respondents were asked what kind of physician’s work they would most preferably do. They were further asked what work they assumed they would be doing in the year 2020. Results Altogether 72% were working in public primary health centres and 14% in the private sector. Of GPs 53% and of GP trainees 70% would most preferably work in health centres. Of GPs 14% would most preferably work as private practitioners and 9% as occupational health physicians. Sixteen per cent assumed they would be working as private practitioners and 35% assumed they would be retired in the year 2020. Of GP trainees 57% assumed they would be working as health centre physicians in 2020. Conclusions According to the present findings many experienced GPs will leave their work as a health centre physician. Moreover, several GP trainees do not consider health centre physician’s work as a long-term career option. These trends may in the future reflect a recruiting problem in many primary health centres.